Bacterial etiology of otitis media and their antibiogram among patients attending tertiary care hospital - Sharma, Ashish; Pyadala, Nagababu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Otitis media is one of the common infection prevalent worldwide. Chronic ear infection in older children can cause hearing loss which leads difficulty in communication, learning and social adjustment. It can result to severe disability, death due to central nervous system disorder in developing countries. Hence, the present study aimed to determine the bacteriological profile and its antibiogram of ear infection. Methods: This study conducted in ENT department of MNR Medical College and Hospital during the period of October 2019 to January 2020. Results: A total of 120 patients were included in this study. Among the total, 70 were adult (58.3%), age group ranges between 20-55 years and 50 were children (41.6%). Bacterial isolates from ear swab included; Staphylococcus aureus 28, Pseudomonas 19, Klebsiella spp 15, Proteus spp 10, Escherichiae coli 7, Enterobacter spp 4 and Citrobacter spp 2. Overall bacteria mostly sensitive to drugs like pipercillin tazobactum (85%), amikacin (90%) and gentamycin (90.2%). Other than these drugs ampicillin (90.1%), cefazolin (90%), cefuroxime (89.4%), ceftriaxone (81%), oxacillin (83.4%), penicillin (88.2%) showed highly resistant to bacterial isolates. Conclusions: Therefore, it is clear from this study that, most of the prescribed drugs were resistant to bacteria isolated from ear infection. Hence it is mandatory to include culture and sensitivity report to manage the cases of otitis media.